Environmental methods used by veterinary centres to reduce stress of cats and dogs during practice visits. (2nd February 2019) - Williams, Taylor; Carroll, Aisling; Montrose, V. Tamara
Abstract : Background: The veterinary practice can be a stressful environment for pets. The stress animals experience when visiting the practice can impact on health, welfare and the likelihood of owners regularly visiting the practice. A number of different approaches have been suggested to be beneficial in reducing stress at the veterinary practice however the methods that practices use to try and reduce stress in animals during veterinary visits, and the reasons for the use of these approaches, has not been determined. Aim: The aim of this study was to determine what methods veterinary practices in the UK use to try to reduce stress in animals during veterinary visits, and gather the views of veterinary staff on the efficacy of these practices. Method: Veterinary practices in the UK (n=45) completed an online mixed methods questionnaire providing information on the practice's use of separate waiting rooms, treat feeding, rehearsal visits, correct handling of animals, appeasing pheromones and sensory enrichment. The reasons why these approaches were or were not used, and the participants' views on whether these practices reduced stress during veterinary visits were also determined. Results: The majority of practices surveyed fed treats to animals during veterinary visits, offered rehearsal visits to animals and their owners, used appeasing pheromones in the practice and stated that they used correct handling techniques for different species during consultations. In addition, the majority of practices surveyed did not have more than one waiting room or use a television or auditory device to try and reduce stress in animals during veterinary visits. The majority of participants believed that separate waiting rooms, rehearsal visits, treat feeding, appeasing pheromones, sensory enrichment and correct handling can reduce stress in animals during veterinary visits. Conclusion: A range of methods are used by veterinary practices within the UK to attempt to reduce stress in animals during veterinary visits. Greater consideration of methods to facilitate separation of species where distinct waiting rooms are not feasible, for example via implementing appointments for cats and dogs on different days and times, would be beneficial. In addition, veterinary staff should consider utilising classical or specially designed species-specific music in the veterinary practice as this may help mitigate the stress of cats and dogs visiting the practice.